Fern Pattern of Cervico-Vaginal Mucus in Relation to Fertility in Crossbred Cows and Heifers - Ningwal, D.; Nema, S.P.; Kumar, S.; Kushwah, A.; Shivhare , M. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
This study was carried out on crossbred cows and heifers 20 each belonging to Dairy farm of the College of Veterinary Sciences & A.H. Mhow and clinical cases of progressive farmers brought for AI to the Teaching Veterinary Clinical Complex and at the doorstep of farmers in nearby villages. The cervico-vaginal mucus (CVM) samples were collected from the animals at oestrus before AI and were immediately evaluated for physical properties particularly fern pattern. Pregnancy was confirmed by rectal palpation after 2 months of insemination. Physical profile revealed that the variations in per cent incidence of typical, atypical and nil fern patterns of CVM samples were highly significant (P<0.01) in both the groups of conceived and non-conceived cows and heifers.